Vitamin E-coated tympanostomy tube insertion decreases the quantity of free radicals in tympanic membrane - (:unkn) unknown (WILEY, 2006)
Objective: Tympanosclerosis is a common sequela of ventilation tube treatment of otitis media with effusion causing hearing disability. It is associated with an increased production of free radicals (also known as reactive oxygen species) after myringotomy. Vitamin E is a scavenger of different free radicals by working as an antioxidant. The aim of the present study was to evaluate the effect of vitamin E-coated tympanostomy tube insertion at quantity of free radicals in rat tympanic membrane. Methods: This prospective, controlled animal study consisted of male Sprague-Dawley rats divided into two groups of 10 animals each. Ordinary silcone tubes were applied to the right ears of the first group and vitamin E-coated silcone tubes were applied to the right ears of the second group. The left ears were used as controls. Then, the animals were killed and chemiluminescence measurements were made for tympanic membranes. Results: Reactive oxygen species levels (ROS) were significantly increased in right ears of the first group when compared with the control ears (P <.0001), and the levels were statistically significant decreased in right ears of the second group as compared with the operated ears of the first group (P <.0001). The free radical levels of right and left ears in the second group were similar. Conclusions: Our results indicate that vitamin E-coated tube insertion decreases the quantity of reactive oxygen species in tympanic membrane after myringotomy and tympanostomy tube insertion.
Keywords: vitamin E coating; rats; ventilation tube; free radicals; MYRINGOSCLEROSIS